2015
DOI: 10.5614/j.eng.technol.sci.2015.47.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight and Structural Properties of Biodegradable PLA Synthesized with Different Catalysts by Direct Melt Polycondensation

Abstract: Abstract. Production of biodegradable polylactic acid (PLA) from biomassbased lactic acid is widely studied for substituting petro-based plastics or polymers. This study investigated PLA production from commercial lactic acid in a batch reactor by applying a direct melt polycondensation method with two kinds of catalyst, γ-aluminium(III) oxide (γ-Al 2 O 3 ) or zinc oxide (ZnO), in reduced pressure. The molecular weight of the synthesized PLA was determined by capillary viscometry and its structural properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…As can be seen in Figure 1, the raw PJS had 8 functional groups. Two bands at a wavenumber of approximately 3635-3765 cm -1 with peaks at 3732 and 3645 cm -1 were assigned to O-H stretching of hydroxyl groups [17,26,34,35]. These bands had the highest transmittance compared to the other groups, i.e.…”
Section: Functional Groups Of the Samplesmentioning
confidence: 99%
“…As can be seen in Figure 1, the raw PJS had 8 functional groups. Two bands at a wavenumber of approximately 3635-3765 cm -1 with peaks at 3732 and 3645 cm -1 were assigned to O-H stretching of hydroxyl groups [17,26,34,35]. These bands had the highest transmittance compared to the other groups, i.e.…”
Section: Functional Groups Of the Samplesmentioning
confidence: 99%
“…The hypothesis is supported by previous studies demonstrating that metal oxides can be used as metal sources for ZIF-8 formation [ 71 ], while ZrO 2 can be used for UiO-66 [ 72 ] synthesis, as well as other reports [ 67 , 73 ] that showed the ability of porous Al 2 O 3 filters to be modified with organic chemicals such as dopamine through a hydroxide-induced covalent reaction [ 67 ]. Furthermore, previous studies showed that a filter’s well-developed porosity and relatively high surface area, large pore volume, and abundant weak Lewis acid sites are essential to promote direct attachment of active molecules [ 74 , 75 ] (here, the FDCA). Such active molecules were further able to incorporate and disperse well into the individual filters’ channels to thus serve as active catalytic species [ 76 ]; such species are all needed for the MIL-160 formation.…”
Section: Resultsmentioning
confidence: 99%
“…The solution within the polymerization reactor was continuously stirred at a speed of 100 rpm and at temperature of 180 °C for 5 hours. A similar experimental set up and operating conditions were reported in our previous research paper [10].…”
Section: Synthesis Of Pdlla and Pllamentioning
confidence: 87%